Materials properties and device applications of semiconducting bismuth oxyselenide - Li, Menglu; Chen, Pei; Zhao, Yan; Zhao, Mei; Leng, Huaqian; Wang, Yong; Ali, Sharafat; Raziq, Fazal; Wu, Xiaoqiang; Yi, Jiabao; Xiao, Haiyan; Qiao, Liang (InfoMat, 2024)
Layered two‐dimensional (2D) materials have garnered marvelous attention in diverse fields, including sensors, capacitors, nanocomposites and transistors, owing to their distinctive structural morphologies and superior physicochemical properties. Recently, layered quasi‐2D materials, especially layered bismuth oxyselenide (Bi2O2Se), are of particular interest, because of their different interlayer interactions from other layered 2D materials. On this basis, this material offers richer and more intriguing physics, including high electron mobility, sizeable bandgap, and remarkable thermal and chemical durability, rendering it an utterly prospective contender for use in advanced electronic and optoelectronic applications. Herein, this article reviews the recent advances related with Bi2O2Se. Initially, its structural characterization, band structure, and basic properties are briefly introduced. Further, the synthetic strategies for the preparation of Bi2O2Se are presented. Furthermore, the diverse applications of Bi2O2Se in the field of electronics and optoelectronics, photocatalytic, solar cells and sensing were summarized in detail. Ultimately, the challenges and future perspectives of Bi2O2Se are included. Oxyselenide Bi2O2Se has emerged as a new type of layered quasi‐2D materials, drawing considerable attention recently due to its excellent physicochemical properties. This review focused on the recent progress related to Bi2O2Se, encompassing structural characteristics, fundamental properties, preparation techniques, and potential applications in devices, which show its great potential for future‐generation electronics and optical technology.